Evaluating the Spin-Off Readiness of Sharia Business Units for Islamic Banking Expansion in Indonesia - Dja’akum, Cita Sary; Huda, Nur; Ryandono, Muhamad Nafik Hadi; Mujibatun, Siti; Mursyidi, Ach Fatayillah (Economica: Jurnal Ekonomi Islam, 2024)
This study aims to evaluate the readiness of Sharia Business Units (SBUs) in Indonesia to undertake the mandated 2023 spin-off, which would result in these units operating independently from their parent banks. The research employs a qualitative approach, with data collected through documentation and literature review. The study focuses on 20 SBUs, which include one unit from a state-owned enterprise (BUMN), 13 units from regionally-owned enterprises (BUMD), and six units from private banks. Findings indicate that approximately 50% of these SBUs are not sufficiently prepared to separate from their parent institutions due to constraints in assets, capital adequacy, and health metrics. This lack of preparedness is compounded by deficiencies in infrastructure and human resources, which collectively affect the financial, operational, and human capital stability of these units. Consequently, the findings suggest that most SBUs are not ready for a spin-off by 2023. Policy implications: The findings underscore the need for regulatory and developmental support to strengthen SBUs prior to spin-off. The study recommends that future policy address the capital and human resource limitations in Islamic banking to ensure successful spin-offs and sustainable growth in the sector.